To divide the polynomial \( 4x^4 + 4x - 10 \) by \( 2x^2 - 3 \), we can use polynomial long division. Let's go through the steps:
-
Divide the first term: \[ \frac{4x^4}{2x^2} = 2x^2 \]
-
Multiply: \[ 2x^2 \cdot (2x^2 - 3) = 4x^4 - 6x^2 \]
-
Subtract: \[ (4x^4 + 4x - 10) - (4x^4 - 6x^2) = 6x^2 + 4x - 10 \]
-
Repeat the process with the new polynomial \(6x^2 + 4x - 10\):
- Divide the first term: \[ \frac{6x^2}{2x^2} = 3 \]
- Multiply: \[ 3 \cdot (2x^2 - 3) = 6x^2 - 9 \]
- Subtract: \[ (6x^2 + 4x - 10) - (6x^2 - 9) = 4x - 1 \]
Now we have completed the division.
The quotient is \( 2x^2 + 3 \) and the remainder is \( 4x - 1 \).
Thus, the correct answer is:
B: The quotient is \( 2x^2 + 3 \). The remainder is \( 4x - 1 \).